2008
DOI: 10.1590/s1676-06032008000400022
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenia e aspectos comportamentais da larva de Phasmahyla guttata (Lutz, 1924) (Amphibia, Anura, Hylidae)

Abstract: O gênero Phasmahyla Cruz, 1990 é composto por pequenos anuros, cujas desovas são depositadas em folhas acima de córregos na mata. Seus girinos são neustônicos e apresentam funil bucal dorsal. Na cidade do Rio de Janeiro o gênero está representado por P.guttata (Lutz 1924). Girinos desta espécie foram coletados no Rio dos Macacos, Horto Florestal, Rio de Janeiro e sua ontogenia foi estudada. A larva eclode no estágio 25 (com cerca de 16,5 mm), permanecendo neste estágio até um comprimento médio de 18,4 mm. O fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Although this first record is still not enough to generalize for all populations of the species, our observations agree with other studies conducted on other species of Phyllomedusinae, such as P. vaillanti, and even on other species of the genus Phasmahyla like P. guttata and P. jandaia (Lutz Lutz, 1939;Branch, 1983;Eterovick Sazima, 1999;Surova, 2006;Costa Carvalho-e-Silva, 2008) …”
supporting
confidence: 91%
“…Although this first record is still not enough to generalize for all populations of the species, our observations agree with other studies conducted on other species of Phyllomedusinae, such as P. vaillanti, and even on other species of the genus Phasmahyla like P. guttata and P. jandaia (Lutz Lutz, 1939;Branch, 1983;Eterovick Sazima, 1999;Surova, 2006;Costa Carvalho-e-Silva, 2008) …”
supporting
confidence: 91%
“…This hypothesis received support from observations in the field and captivity. Shoals of Phasmahyla tadpoles have been observed with the oral disk in contact with the water surface for long periods (Costa & Carvalho‐e‐Silva, 2008). Savage (1968, 2002) reported that tadpoles of Silverstoneia feed on the surface by rotating their oral disk; larvae of M. montanae have also been observed in such position (Hoff et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that Phasmahyla guttata tadpoles undergo ontogenetic variations in development ( Costa & Carvalho-e-Silva, 2008 ). We verify such variation in P. lisbella sp.…”
Section: Discussionmentioning
confidence: 99%